CALENDARIO POLÍNICO DE ESPECIES POTENCIALMENTE ALERGÓGENAS Y SU RELACIÓN CON PARÁMETROS METEOROLÓGICOS EN VILLA VENTANA, PROVINCIA DE BUENOS AIRES - Graciela M. Benedetti; Barbara S. Sastre; Alicia M. Campo (Boletín Geográfico)
Urban trees ensure multiple social and environmental benefits for residents in urban areas. But what will happen if these species are not the correct ones?. The inclusion of some kind of trees is not recommended because its pollen causes certain sensitivity in humans. If a plant contains antigens capable of triggering an anaphylactic phenomenon in the human body it must be considered allergenic. An anaphylactic process is one that increases the body's sensitivity with respect to a given substance, caused by an exposition to a certain dose. The plants should be mainly anemophilous (although under certain conditions the pollen that is carried by insects also produce allergy); must be located around human habitats; and the pollen must be capable of being transported easily in the wind. Then, this is possible to particles with size between 18 and 60 microns, these particles are easily moved around in the atmosphere because of minor effect of gravity. The aim of this study is to know which tree species in Villa Ventana, Tornquist, Buenos Aires province, aren´t adecuated because of their allergenic pollen. So, in that context, the construction of a calendar is recommended in order to know the behavior of the pollen species. If we consider that Villa Ventana is seen as a recreational and nice meeting place for activities in contact with nature to enhance health, tree species that cause irritation in humans should be avoided.